Korelasi Self Esteem Dengan Tingkah Laku Sosial Serta Implikasinya Pada SD Muhammadiyah IV Padang - Nidia Suryani; Hamidah Rahim (Jurnal Riset Madrasah Ibtidaiyah, 2022)
This research was initiated by the fact that there is no self-esteem in students based on their environmental conditions. Peers, past experiences, mindset, gender, social status, achievements, values, beliefs, and upbringing are factors that influence this condition. The purpose of this study was to describe self-esteem, describe children's social behavior, and understand the relationship between self-esteem and children's social behavior, and understand the implications for guidance and counseling services. This research uses a quantitative method with a correlational descriptive type. The population of this study was 180 students of primary school Muhammadiyah IV Padang. The sample is 150 students selected by random sampling technique. The results show that in general students' self-esteem is in a low category, students' social behavior is in the medium category, while the correlation between self-esteem and social behavior is negative, where r count r table, then Ho is accepted or the independent variable does not exist. significant correlation with the dependent variable. The implication is that guidance and counseling services can be implemented in the form of information services, content mastery, and group guidance services that are carried out for each class. This implication is expected to be an input for teachers in increasing students' self-esteem and social behavior.